Literasi Digital Pembelajaran Pendidikan Agama Islam Pada MA Nurul Qur’an Bogor - Elis Lisyawati; Mohsen Mohsen; Umul Hidayati; Opik Abdurrahman Taufik (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
Many madrasas do not yet have the readiness and ability to implement digital literacy in learning Islamic Religious Education (PAI) in its various aspects, such as aspects of teacher readiness, infrastructure, curriculum, learning strategies, and the lack of culture in implementing digital literacy, especially private madrasas which have many limitations. . supposedly, the development of advances in digital technology that penetrates all lines of life including the education sector, learning should be carried out by utilizing the presence of digital technology as a means to support smooth learning. This study uses qualitative methods, with phenomenological and sociological approaches. Data collection was carried out through in-depth interviews, participatory observations, and document studies. The results of the study show that the implementation of Digital Literacy in PAI Learning at MA Nurul Qur'an has worked well, which can be seen in several indicators, such as: digital-based PAI learning can run smoothly; madrasas provide support in the form of policies on providing facilities, procuring teachers, and learning funding; in practice PAI learning is carried out web-based and social media which is carried out through class learning, laboratory learning, and online; in PAI learning, monitoring and evaluation have been carried out by the head of the madrasa and teachers both routinely and incidentally.